Acute single dose of ketamine relieves mechanical allodynia and consequent depression-like behaviors in a rat model. (19th September 2016) - Zhang, Guang-Fen; Wang, Jing; Han, Jin-Feng; Guo, Jie; Xie, Ze-Min; Pan, Wei; Yang, Jian-Jun; Sun, Kang-Jian
Highlights: Inflammatory pain can induce depression-like behaviors in rats. Ketamine relieves inflammatory pain and depression-like behaviors of rats. Ketamine downregulates inflammatory cytokines and IDO/KYN pathway in rat hippocampus. Abstract: Both chronic pain and depression are debilitating diseases, which often coexist in clinic. However, current analgesics and antidepressants exhibit limited efficacy for this comorbidity. The present study aimed to investigate the effect of ketamine on the comorbidity of inflammatory pain and consequent depression-like behaviors in a rat model established by intraplantar administration of complete Freunds adjuvant (CFA). The mechanical withdrawal threshold, thermal withdrawal latency, open field test, forced swimming test, and sucrose preference test were evaluated after the CFA injection and ketamine treatment. The hippocampus was harvested to determine the levels of interleukin (IL)-6, IL-1β, indoleamine 2, 3-dioxygenase (IDO), kynurenine (KYN), 5-hydroxytryptamine (5-HT), and tryptophan (TRP). The inflammatory pain-induced depression-like behaviors presented on 7 days and lasted to at least 14 days after the CFA injection. Single dose of ketamine at 20 mg/kg relieved both the mechanical allodynia and the associated depression-like behaviors as demonstrated by the attenuated mechanical withdrawal threshold, reduced immobility time in the forced swim test, and increased sucrose preference after ketamine treatment. The total distance had no significant change after the CFA injection or ketamine treatment in the open field test. Simultaneously, ketamine reduced the levels of IL-6, IL-1β, IDO, and KYN/TRP ratio and increased the 5-HT/TRP ratio in the hippocampus. In conclusion, acute single dose of ketamine can rapidly attenuate mechanical allodynia and consequent depression-like behaviors and down-regulate hippocampal proinflammatory responses and IDO/KYN signal pathway in rats.